10-year follow-up after first stroke: Impact on life - Aldís Edda Ingvarsdóttir 1994- (2019)
Background and purpose: Stroke is the second leading cause of death worldwide and those who survive are often left with long-term impairments. Little is known about survival rate and the impact on life for individuals after first stroke in Iceland. The aim of this cross-sectional study was to describe the 10-year outcome of how first stroke has impacted life of adults in Iceland. This is the first long-term follow-up study reported in Iceland. Methods: The research data for this study is built on a first-time stroke incidence study that was conducted in Iceland. Participants from that study were re-identified using the Icelandic medical record system. We identified 96 survivors and sent them a questionnaire that included the Icelandic version of the Stroke Impact Scale 3.0. The questionnaire also included questions on socio-demographics. Results: Overall, 55 individuals responded (57% response rate). The sample had similar characteristics as the incidence study. The mean age was 73.1 years and the majority lived in the Capital Area. Median scores from the SIS were fairly high. There was no difference between SIS scores and gender or residence. There was an age difference in most SIS domain scores; younger groups had higher median scores than older groups. Conclusion: In general, Health related qualities of life (HRQoL) among stroke survivors in Iceland is good 10 years after first stroke. Older individuals reported poorer HRQoL than younger people.